EU security strategies extending the EU system of security governance - Economides, Spyros; Sperling, James (Routledge studies in European security and strategy, 2018)
This volume offers a coherent analysis of the European Union's security strategies within a comparative framework. The volume integrates a 'new' EU security strategy into the analysis to determine whether and to what extent it reinforces the successes or overcomes the limitations of the current set of security strategies governing the EU and its member states.